A relação entre o microcrédito e o capital social : o caso do CEAPE PI - Araujo, Allen da Costa (2011)
This study consists of a study on the presence of relationship between social capital and solidarity groups to endorse the Center for Support to Small Businesses - CEAPE - PI, the capital was measured by confidence levels and associations, considering trust as the expectations want, and learned associations between people and how the interactions among members within a group and between groups. The central research question seeks to identify whether there are linkages between the levels of social capital and the profile of members of the solidarity group CEAPE-PI. The overall objective is to analyze the level of social capital and whether these vary with the change in the profile of the solidarity group members. The method adopted in perspective cross-examined the level of social capital found in 300 of solidarity group members, collected through a survey research related to the profile of the solidarity group members, obtained with the CEAPEPI. The data show that micro-credit groups have relatively high levels for most variables, but to relate to the profile of microcredit results demonstrate the interesting points of analysis